Gender and nation in the Spanish modernist novel - Johnson, Roberta, 1942- (Vanderbilt University Press, 2003)
Offering a fresh, revisionist analysis of Spanish fiction writers from 1900 to 1940 and how they practiced differing forms of modernism.